Colonic stricture as a complication of haemolytic uraemic syndrome - Megan Grinlinton; Stephen Evans; Tonya Kara (Elsevier, 2017)
Haemolytic uraemic syndrome (HUS) is an infectious disease that can rapidly become life-threatening in the paediatric population. A number of long-term complications may arise from HUS including the rare development of colonic strictures. In this case report, we present two cases with similar presentations of colonic strictures following HUS. Case 1 is a 17-month-old female who developed HUS and multiple complications including a sigmoid colonic stricture. Once the stricture was resected, her recovery was rapid and complete. Case 2 is a 3-year-old male who developed severe HUS requiring dialysis. After developing a small bowel obstruction, a laparotomy demonstrated caecal disease, pan-colonic inflammation, a calcified appendix and a strictured descending colon. A second operation revealed strictures at the transverse, descending and sigmoid colon. Once the diseased part of bowel had been removed his recovery was complete. This report demonstrates the diagnostic difficulty and patient morbidity that may arise from post-HUS colonic strictures. A contrast study is the recommended investigation of choice in patients presenting with ongoing gastrointestinal symptoms after an acute infection with HUS.